2022
DOI: 10.1111/ijcs.12812
|View full text |Cite
|
Sign up to set email alerts
|

Applying the theory of reasoned action to examine consumers' attitude and willingness to purchase organic foods

Abstract: The organic food market has emerged as a growing trend among consumers. The present study examines the relationship between Health Consciousness (HC), Organic Food Knowledge (OFK), Subjective Norms (SN), Price Perception (PP), Environmental Concern (EC), Attitude (ATT), Willingness to Purchase (WP), and Actual Buying Behaviour (ABB) towards organic food. Furthermore, the study explores the mediating effects of ATT and WP in the relationship between the aforesaid variables and ABB. The data was collected from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 162 publications
(352 reference statements)
4
13
1
Order By: Relevance
“…According to the results, the relationships between subjective norms and purchase intention (H2) are not significant, a different result from previous studies (Matharu et al, 2021;Teixeira et al, 2021). A possible explanation may be that there is a total mediation effect of environmental knowledge and health consciousness in the relationship between subjective norms and purchase intention (Kim and Choi, 2005;Kumar et al, 2022;Smith and Paladino, 2010). Multiple mediation models were analysed considering each model in isolation, only with the relationships of the independent variable (subjective norms) with both mediating variables (environmental knowledge and health consciousness) and the dependent variable (purchase intention), as well as of the mediators with the model-dependent variable.…”
Section: Resultscontrasting
confidence: 61%
See 3 more Smart Citations
“…According to the results, the relationships between subjective norms and purchase intention (H2) are not significant, a different result from previous studies (Matharu et al, 2021;Teixeira et al, 2021). A possible explanation may be that there is a total mediation effect of environmental knowledge and health consciousness in the relationship between subjective norms and purchase intention (Kim and Choi, 2005;Kumar et al, 2022;Smith and Paladino, 2010). Multiple mediation models were analysed considering each model in isolation, only with the relationships of the independent variable (subjective norms) with both mediating variables (environmental knowledge and health consciousness) and the dependent variable (purchase intention), as well as of the mediators with the model-dependent variable.…”
Section: Resultscontrasting
confidence: 61%
“…In addition to the traditional influences of the constructions proposed by the TPB, some studies seek to observe the effects of moderation, mediation and relationships between the predictors of intention to consume organic foods (Kim and Choi, 2005;Kumar et al, 2022;Smith and Paladino, 2010). For example, Dursun et al (2019) state that the environmental psychology literature provides empirical evidence on the effect of subjective knowledge on pro-environmental behaviours.…”
Section: Incorporating Additional Constructs In the Tpbmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have confirmed that consumer behavior is led by behavioral intention, which is the outcome of two antecedents, attitudes and subjective norms (Pookulangara, Hawley, & Xiao, 2011). The causal relationships of TRA were validated in various consumption settings such as clothing purchases (Belleau, Summers, Xu, & Pinel, 2007;Kim, Kim, & Kumar, 2003), online shopping (Ashokkumar & Nagarajan, 2021), social media influences (Copeland & Zhao, 2020), mall patronage (Evans, Christiansen, & Gill, 1996), and organic purchases (Kumar, Gupta, Kumar, Singh, & Singh, 2022). Another study objective is to explore how TRA predicts millennials and Gen Z consumers' omnichannel shopping behaviors.…”
Section: Introductionmentioning
confidence: 94%